Monumental conflicts
1 online resource (249 pages)
Keywords: Monumental Conflicts examines 20th century wars from the First World War to the First Gulf War, each chapter analyzing how public memory has evolved over time. The chapters raise fascinating questions about war and memory: Why are wars remembered as they are? What factors drive changes in public perception? What implications arise from remembering and commemorating a war or particular aspects of a war? What does public memory of a war say about us as a society? The volume is divided into three sections focusing on political evolution, negotiated memories of war, and national pride and covers international wars from Afghanistan to Vietnam and German deserter monuments to Vietnamese war tourism.